DYSFUNCTION OF THE VASCULARS ENDOTHELIA IN THE TRAUMATIC BRAIN INJURY - Борщикова, Тамара Ивановна; Епифанцева, Наталья Николаевна; Кан, Сергей Людовикович; Лызлов, Андрей Николаевич (Medicine in Kuzbass, 2019)
Objective – in this article to studied of 53 patients with severe traumatic brain injury (TBI) from 1-st to 14 days after trauma. The dynamics of proteins endothelin-1 (ET-1) and the factor von Willebrand (FW) was assessed in groups of patients: survivors and deceased patients and have or not purulent-inflammatory complications. The control group consisted of 21 people. We are study the dynamics of the ET-1 and the FW in the post-traumatic period and determine its roles in predicting of the development of purulent-inflammatory complications and the outcome from TBI.Methods. On 1, 4, 7, 10, 14 days after the TBI we determined levels of ET-1 by the method of solid-phase enzyme immunoassay by the test systems in the serum of the venous blood. The FW was assessed by the ELISA test system «Technoclone» in set of equipment for ELISA (reader, washer, shaker incubator). In the course of 1, 7 and 14 days were studied of the proinflammatory cytokines IL1β, TNFa, IL6, IL8 by the commercial test systems «11 plex» on the Citomics FC-500 flow cytometer «Becman Coulter».Results. The markers of endothelial dysfunction the ET-1 and the FW increased from 1 to 14 days in patient which severe traumatic brain injury. The maximum values of ET-1 were observed in subgroups deceased patients and in patients with inflammatory complications on 10-14 days. The ET-1 was higher than exceeding values the control group by 2,0-3,7 times. The highest values of the FW were observed in patients on 4-14 days, exceeding the values of the control group by 1,4-1,5 times. The increase in proinflammatory cytokines IL6 and IL8 significantly correlated with the level of the ET-1, and IL1β and TNFa with the level of the FW.Conclusions. The endothelial dysfunction in severe traumatic brain injury according to the increase levels of the ET-1 and FW. The FW acted as predictors of the outcome from TBI.
Keywords: severe traumatic brain injury; endothelin-1; factor von Willebrand; purulent-inflammatory complications